Evaluasi Penerapan Sistem Manajemen Keselamatan Pertambangan PT. Pesona Khatulistiwa Nusantara Tahun 2022 - sulfikar, sulfikar; Syafei, Abdullah (Journal of Religion and Public Health, 2023)
AbstractThe mining safety management system is an important aspect that needs to be considered in mining companies, because the success of the company's production is also determined by worker safety. In Indonesia, the Mining Safety Management System (SMKP) must be implemented by mining companies and mining service companies, in accordance with Minister of Energy and Mineral Resources Regulation No. 26 of 2018. This regulation aims to evaluate the effectiveness of planned, measurable, structured and integrated mining safety management. This research aims to evaluate the implementation of the Mining Safety Management System at PT Pesona Khatulistiwa Nusantara in 2022 using primary data and secondary data. Primary data was collected through observation, interviews and documentation. The informants in this research were 2 SHES Managers and SHS Superintendents, 3 Operation Division managers, 3 field personnel from each business activity area of PT Pesona Khatulistiwa Nusantara. Secondary data was collected from various sources such as academic literature, government regulations related to mining safety, accident or inspection reports, company policies, and internal documents of PT Pesona Khatulistiwa Nusantara. The results of the research show that the implementation of the Mining Safety Management System at PT Pesona Khatulistiwa Nusantara has not yet been completed in accordance with the Decree of the Director General of Mineral and Coal of the Ministry of Energy and Mineral Resources Number 185.K/37.04/DJB/2019, there are still several elements that have not been implemented or are even still in process and are not yet running properly. planning that is not yet in accordance with the conditions and programs set, organizational and personnel elements that have not been socialized optimally, implementation elements that have not all been implemented, monitoring, evaluation and follow-up elements that still have deficiencies, documentation elements that have not all been socialized, and management review elements the implementation of which does not yet involve the company's highest leadership and has not been carried out in a planned manner.Keywords: Evaluation, Mining safety, Mining safety management system